Governance Strategies and Welfare Effects: Vertical Integration and Contracts in the Catfish Sector in Vietnam - Neda Trifković (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2013)
Using an original dataset from the Vietnamese catfish sector, we study the impact of vertical coordination options on household welfare and the implications of different stages of vertical coordination for the success of the whole sector. The welfare gain from contract farming and employment on processor-owned estate farms is estimated using a maximum simulated likelihood estimator. Our results show positive welfare effects from participating in contract farming, but not from employment on processor-owned estate farms. The results imply that contract farming presents opportunities for economic growth, but additional effort is required to make the contracts more accessible to smallholders.
Keywords: D02; D31; O17; L14; L24; 330; vertical coordination; catfish; maximum simulated likelihood; agri-food transformation; Vietnam